2021
DOI: 10.1177/03000605211042975
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of ferroptosis-related genes in ulcerative colitis

Abstract: Objective The aim of this study was to identify and validate ferroptosis-related markers in ulcerative colitis (UC) to explore new directions for UC diagnosis and treatment. Methods We screened UC chips and ferroptosis-related genes from the Gene Expression Omnibus (GEO), FerrDb, and GeneCards databases. The differentially expressed genes (DEGs) and ferroptosis-related DEGs between the UC group and normal controls were analyzed using bioinformatics methods. Enrichment analysis, protein–protein interaction anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
(29 reference statements)
0
18
0
Order By: Relevance
“…However, the mechanism of MUC1 in alleviating lung injury of sepsis was still unclear. In recent years, studies have shown that MUC1 was closely associated with ferroptosis and might be a biomarker related to ferroptosis [ 35 , 36 ]. Our studies indicated that inhibiting the dimerization of MUC1 could significantly reduce the expression level of GPX4, decrease the expression levels of GSH and SOD, improve MDA and MPO, increase the level of lipid peroxides, break mitochondrial membrane, and increase membrane density, thereby stimulating ferroptosis and aggravating lung injury, which proved the close relationship between MUC1 and ferroptosis in the ALI model of sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the mechanism of MUC1 in alleviating lung injury of sepsis was still unclear. In recent years, studies have shown that MUC1 was closely associated with ferroptosis and might be a biomarker related to ferroptosis [ 35 , 36 ]. Our studies indicated that inhibiting the dimerization of MUC1 could significantly reduce the expression level of GPX4, decrease the expression levels of GSH and SOD, improve MDA and MPO, increase the level of lipid peroxides, break mitochondrial membrane, and increase membrane density, thereby stimulating ferroptosis and aggravating lung injury, which proved the close relationship between MUC1 and ferroptosis in the ALI model of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, we also found that the expression level of MUC1 (KL-6) in the plasma of sepsis patients complicated with ARDS was significantly increased and had a good predictive value for early sepsis patients complicated with ARDS [34]. Li Oxidative Medicine and Cellular Longevity in ulcerative colitis through database integration analysis [36]. However, whether MUC1 plays a role in the ferroptosis of ALI/ARDS in sepsis remains obscure, and the specific mechanism needs to be illustrated.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In our previous study, we analyzed the dataset uploaded by Dunn et al using bioinformatic analyses and found that the expression of Cd44 was significantly upregulated after 7 days of carotid artery ligation ( Zhang and Gu, 2022 ). Moreover, it is closely related to ferroptosis and has been studied in ulcerative colitis ( Cui and Chen, 2021 ) and various cancers ( Liu and Jiang, 2019 ; Deng and Zheng, 2021 ; Kozawa and Sekai, 2021 ). However, the role of Cd44 in ferroptosis and IH remains unknown, this is the innovation of our research.…”
Section: Discussionmentioning
confidence: 99%
“…Blocking SLC7A11 transporter activity leads to glutathione depletion and inactivation of phospholipid hydroperoxide glutathione peroxidase 4 (GPX4) and further induces ferroptosis [ 6 , 7 ]. In addition, mucin 1 (MUC1) is a ferroptosis-related gene that forms a complex with xCT and protects against treatment with erastin [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%